The text of the other. Logic of literary remake - Riccardo Stracuzzi (Griseldaonline)
Among the various forms of literary rewriting, it is possible to identify a specific term, the remake, which deserves to be precisely defined in relation to its textual constitution and the principles that govern its construction. In order to better understand this phenomenon, it is necessary to answer some questions: what is the difference between remake and other forms of rewriting? What textual relationship does the remake (as well as other types of closely related derivative texts: the apographs) have with its model (the antigraph)? What are the different and contextual reasons, in relation to the literary market, that drive some actors in this market to produce remakes and other apocryphal texts?